Optimizing Water Hyacinth Management: Distribution Mapping and Management Efforts through a Study in Wedung District, Demak Regency - Cahyo Wulandari; Nisa Amelia; Sausan Adelia Galuh Tri Juasni; Dewi Astutiningtias Lestari; Geraldy Eka Putra Hardiwiyanto; Azzam Rafif Santoso; Gesti Nola Salsabila (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Water hyacinth (Eichhornia crassipes) is an aquatic weed that grows rapidly in shallow and non-flowing waters. In Tempel, Tedunan, and Wedung Villages, Wedung Subdistrict, Demak District, its growth is exacerbated by eutrophication, which is an increase in nutrients due to pollution from agricultural activities and domestic waste. Water hyacinth causes negative impacts, such as blockage of waterways, siltation, and reduction of sunlight penetrating the water, which disrupts the life of the biota below. This community service programs aims to map the distribution of water hyacinth spatially using Geographic Information System (GIS) and solving the problem of water hyacinth eutrophication with simple for harvester and recommendations for distribution strategies for harvested water hyacinth. Through satellite image mapping using ArcGIS software, the water hyacinth was found in Tempel, Tedunan, and alse Wedung Villages in slow current. Water hyacinth in Tempel Village covers area of 52.282 m² and is the worst among the three villages. An Alternative solution is to make a water hyacinth harvesting tool in the form of a simple, cheap, waterproof, and corrosion resistant harvesting fork. In addition, a policy brief was prepared to formulate policy recommendations related to the potential utilization of water hyacinth. The recommendation is to distribute water hyacinth to local artisans to be processed into products of economic value, such as organic fertilizer or handicrafts. This aims not only to reduce environmental impacts, but also improve community welfare through job creation and productive utilization of waste. The results of this programs show that the utilization of technology can be an effective solution in water hyacinth weed management, both from environmental and economic aspects.